2020
DOI: 10.1159/000515327
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Impact in Hospital Healthcare Workers: Development of an Occupational Health Risk Management Program

Abstract: As with the SARS-CoV-1 outbreak in 2003–2004 and the MERS outbreak in 2012, there were early reports of frequent transmission to healthcare workers (HCW) in the SARS-CoV-2 pandemic. Our hospital center identified its first COVID-19 confirmed case on March 9, 2020, in a 6-day hospitalized patient. The first confirmed COVID-19 case in a HCW happened 3 days later, in a nurse with a probable epidemiological link related to the first confirmed patient. Our study’s first objective is to describe and characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A previous study conducted in Indonesia and Portugal showed that positivity rate in medical workers during March-June 2020 was about 5.8% and 6.8%, respectively. 18 , 19 In addition, many patients also limit their visit to the hospital due to risk of COVID-19 infection and limit access to transportation. Consent for surgery also could not be obtained immediately from the patient due to several of the factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study conducted in Indonesia and Portugal showed that positivity rate in medical workers during March-June 2020 was about 5.8% and 6.8%, respectively. 18 , 19 In addition, many patients also limit their visit to the hospital due to risk of COVID-19 infection and limit access to transportation. Consent for surgery also could not be obtained immediately from the patient due to several of the factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…). While major amputations were also higher in the pandemic group (20.2% vs 39.4%, P = .014, Figure 3C), no differences in length of stay (19 (12-24) days vs 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) days, P = .16, Figure 2B) and mortality (14.3% vs 11.3%, P = .76, Figure 3D) were observed between pre-and during the pandemic group. During the pandemic, those with COVID-19 infection (7/71, 9.8%) had more severe infections, worse kidney function, longer waiting time-tosurgery, and higher mortality (Table 3).…”
Section: Figure 2amentioning
confidence: 94%
“…A study suggests a higher chance of infection spread among co-workers in healthcare setting compared to patient-HCW spread. 41 This is the second lesson that can be learned from our study. If HCWs are the first population that spread an emergent infection, stricter work rules need to be applied to them as soon as a new infection is discovered in the area.…”
Section: Discussionmentioning
confidence: 71%